MOTIF TIONGKOK MENINGKATKAN KERJA SAMA DENGAN MEKONG RIVER COMMISSION - Dinda Mei Sari; Yessi Olivia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The focus of this research is to analyze the motives of China to increase cooperation with the Mekong River Commission, an organization whose members are lower Mekong basin countries, namely Thailand, Laos, Cambodia, and Vietnam. China, which is the upper Mekong, was initially not at all interested in working with the MRC and was only content with dialog partner status. However, since the 2000s, China, with its steadily increased power and hegemonic projection in the region, has changed its approach in dealing with the MRC. China has shown a great interest in increasing cooperation with the MRC. This change certainly raises a question to China’s grown interest in MRC.This research uses the neorealism perspective that focuses on how states interact in order to survive the anarchical international system. Neorealism considers that international cooperation will open up opportunities to achieve the power to fulfill national interests, especially to maintain the existence of the state (survival). By becoming a hegemon, a country can influence policies in international cooperation to reach national interests. Data collection in this research was collected through literature study. This research shows that China's motive for increasing cooperation with the MRC is because China needs the energy of the Mekong River to fulfill its growing energy demand. China then built a hydropower dam project on the Mekong River. In responding to various criticisms and rejection of dam construction, China used its hegemonic status by persuading the downstream countries through investment and following cooperation rules that benefited China economically. Keywords: China, Mekong River Commission, Hegemon, Mekong River and Hydropower